Analisis Kesenjangan Penguasaan Teori Tajwid dengan Praktik Membaca Al-Qur'an pada Peserta Didik - Andini, Aulia Tri; Amriyah, Chairul; Octafiona, Era (Paedagogie, 2026)
This study aims to analyze the gap between mastery of tajwid theory and Qur’anic reading practice among eleventh-grade students. The research employed a quantitative approach with a descriptive comparative design. The population consisted of 306 students, with 52 respondents selected using cluster random sampling. Data were collected through theoretical and practical reading tests. Data analysis included normality, homogeneity, linearity, Pearson correlation, and paired sample t-test. The findings revealed that the data were normally distributed and homogeneous. The correlation test indicated no significant relationship between theoretical mastery and reading practice (r = 0.228; Sig. = 0.105). However, the comparative test showed a significant difference between theoretical and practical scores (Sig. = 0.000), with theoretical scores higher than practical scores. These findings indicate a substantial gap between tajwid theoretical mastery and practical Qur’anic reading skills.